2017
DOI: 10.1007/s11430-017-9074-6
|View full text |Cite
|
Sign up to set email alerts
|

Origin and structures of solar eruptions I: Magnetic flux rope

Abstract: Coronal mass ejections (CMEs) and solar flares are the large-scale and most energetic eruptive phenomena in our solar system and able to release a large quantity of plasma and magnetic flux from the solar atmosphere into the solar wind. When these highspeed magnetized plasmas along with the energetic particles arrive at the Earth, they may interact with the magnetosphere and ionosphere, and seriously affect the safety of human high-tech activities in outer space. The travel time of a CME to 1 AU is about 1-3 d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
97
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(104 citation statements)
references
References 323 publications
3
97
0
4
Order By: Relevance
“…Indeed, the relevance of MFRs with solar flares and eruptions has also been extensively evidenced from both observations and coronal magnetic field reconstructions. For instance, X-ray and EUV sigmoid, filament, EUV hot channel, and coronal cavity are invoked as indirect observations of coronal MFRs (e.g., see a recent review paper by Cheng et al 2017). Using nonlinear force-free field (NLFFF) extrapolations from vector magnetograms, which is a basic tool for unraveling the 3D information of solar coronal magnetic field, MFRs were identified frequently (e.g., see another recent review by Guo et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the relevance of MFRs with solar flares and eruptions has also been extensively evidenced from both observations and coronal magnetic field reconstructions. For instance, X-ray and EUV sigmoid, filament, EUV hot channel, and coronal cavity are invoked as indirect observations of coronal MFRs (e.g., see a recent review paper by Cheng et al 2017). Using nonlinear force-free field (NLFFF) extrapolations from vector magnetograms, which is a basic tool for unraveling the 3D information of solar coronal magnetic field, MFRs were identified frequently (e.g., see another recent review by Guo et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The pre-eruptive configuration of CMEs/flares is often believed to be a magnetic flux rope (MFR), which may contain a filament/prominence (Kuperus & Raadu 1974;van Tend & Kuperus 1978;van Ballegooijen & Martens 1989;Mackay et al 2010;Schmieder et al 2013;Cheng et al 2017). In this system, filament material is preferentially collected in the magnetic dips of the MFR, which provide an upward Lorenz force that naturally balances gravity (Low & Hundhausen 1995;Gibson et al 2004;Gibson & Fan 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been sug-gested that kink instability could be associated with small-scale (nano) flares [e.g., Browning et al, 2008]. Meanwhile, plenty of literature is available to present abundant evidence in theories, numerical simulations and observations on how the eruptions of filaments and CMEs are related to kink-unstable magnetic flux ropes [e.g., Rust and Kumar, 1996;Kliem et al, 2004;Török and Kliem, 2005;Williams et al, 2005;Guo et al, 2010;Kumar et al, 2012;Liu et al, 2016c;Cheng et al, 2017;Vemareddy et al, 2017]. Recently, Wang et al [2016] has further identified the magnetic twist inside post-eruption flux ropes in the heliosphere from analyzing 115 magnetic clouds observed at 1 AU.…”
Section: Introductionmentioning
confidence: 99%